Security, privacy, and forensics issues in big data - Joshi, Ramesh C., editor 631945; Gupta, Brij B., editor 631944 (Hershey, Pennsylvania : IGI Global, 2020)
Chapter 1. Securing the cloud for big data -- Chapter 2. Big data: challenges and solutions -- Chapter 3. Human factors in cybersecurity: issues and challenges in big data -- Chapter 4. Security and privacy challenges in big data -- Chapter 5. Cloud-centric blockchain public key infrastructure for big data applications -- Chapter 6. Security vulnerabilities, threats, and attacks in IoT and big data: challenges and solutions -- Chapter 7. Threat hunting in windows using big security log data -- Chapter 8. Nature-inspired techniques for data security in big data -- Chapter 9. Bootstrapping urban planning: addressing big data issues in smart cities -- Chapter 10. Securing online bank's big data through block chain technology: cross-border transactions security and tracking -- Chapter 11. Enhance data security and privacy in cloud -- Chapter 12. The unheard story of organizational motivations towards user privacy -- Chapter 13. Botnet and Internet of things (IoTs): a definition, taxonomy, challenges, and future directions -- Chapter 14. A conceptual model for the organizational adoption of information system security innovations -- Chapter 15. Theoretical foundations of deep resonance interference network: towards intuitive learning as a wave field phenomenon -- Chapter 16. Malware threat in internet of things and its mitigation analysis -- Chapter 17. Leveraging fog computing and deep learning for building a secure individual health-based decision support system to evade air pollution.